Sediment grain-size, XRF and RockEval datasets for three on-mound cold-water coral mound cores (East Melilla Coral Province, Mediterranean Sea) - Fentimen, Robin; Feenstra, Eline; Rueggeberg, Andres; Hall, Efraim; Vogel, Hendrik; Rosso, Antonietta; Hajdas, Irka; Jaramillo-Vogel, David; Grobéty, Bernard; Adatte, Thierry; Van Rooij, David; Frank, Norbert; et al. (PANGAEA, 2022)
These sedimentological and geochemical analyses were carried out on three on-mound cold-water coral mound cores (MD13-3455G, MD13-3459G and MD13-3462G) recovered in the East Melilla Coral Province (Southeast Alboran Sea, Mediterranean Sea) during the EUROFLEETS cruise MD194 “Gateway” on board the RV Marion Dufresne II in June 2013. The time period of the studied core sections covers the last 15 ky and offers a high-resolution temporal record of the Bølling–Allerød interstadial. The core sites are situated approximately 1 km apart on the crest of Brittlestar Ridge I (35°26.087'N, 2°30.100'W). More precisely, the three datasets presented here correspond to: (1) particle size analysis results determined on the siliciclastic fraction using the Malvern Mastersizer 3000 at the Department of Geology at Ghent University. These analyses were carried out in order to quantify important changes in sediment flux and bottom current velocity. (2) Scanning X-ray fluorescence (XRF) was carried out using the Itrax high-resolution XRF core scanner at the Institute of Geological Sciences, University of Bern, to measure relative element concentration changes in the sediments of the cold-water coral mounds; whereas (3) RockEval6 pyrolysis was carried out at the Laboratory of Sediment Geochemistry at the University of Lausanne (Switzerland) to characterize the organic carbon content of the mound sediments
Keywords: Alboran Sea; Cold-water coral; Grain Size; TOC; XRF